Validitas dan praktikalitas buku teks pelajaran mengintegrasikan CTL dan literasi lingkungan materi gelombang mekanik dan persamaan gelombang untuk siswa SMA kelas XI - Neneng Srikandi (Universitas Negeri Padang, 2020)
The 2013 curriculum is designed to meet the needs of the 21st century that is growing rapidly so that schools are required to change teaching-centered learning approaches into student-centered learning approaches. Learning physics at SMAN 7 Padang is not student-centered. To create student-centered learning, it takes contextual learning resources and environmental literacy. Real conditions indicate the application of CTL and environmental literacy is still relatively low. The purpose of this study is to determine the level of validity and practicality of textbooks that are made for wave material. The type of research used is Research and Development (R&D) according to Sugiyono. The research instrument used was an instrument of validity validated by 3 physics lecturers consisting of 6 components and 57 aspects assessed. The practicality instrument that was practiced by 2 teachers and students at SMAN 7 Padang consisted of 4 components and 37 aspects that were assessed. Based on the results of data from the validity analysis obtained an average value of 92.46 with excellent category. The results of the analysis of the practicality of teachers and students obtained an average value of 89.16 and 92.26 also in the excellent category. So, it can be concluded that textbooks integrate CTL and environmental literacy in the material of mechanical waves and wave equations are valid and practical for high school students in class XI. So the textbook is feasible to use.